Truman Doctrine (1946); Defense Planning Guidance (1991) & The National Security Strategy (2002): the Mackinder & Spykman Dialects revisited (Revista da EGN, 2023)
The aim of this article is to test the hypothesis that HalfordMackinder and Nicholas Spykman’s geopolitical theories,which sustained the grand strategy of the United Stateswith the implementation of 1946 Truman Doctrine, arestill relevant today after their termination. The resultsindicate that the intellectual matrixes were found indocuments of the grand strategy of the United States intwo moments. First, in 1992, in the George Herbert WalkerBush’s government’s Defense Planning Guidance document,formulated by the Pentagon, in February 1992. Second,they were found replicated 10 years after in the first termof President George Walker Bush, inaugurated in 2001. Inthe latter, the theoretical formulations repercussions weredepicted in the official documents Quadrennial DefenseReview (2001) and the National Security Strategy (2002).The article concluded that the authors’ ideas remain validto explain and interpret the actions of the United States’grand strategy in the international scenario.